The Role of Dental Assistants in Modern Dentistry: A Systematic Approach to Improving Dental Care - Shihanah Faihan Alotaibi, Ghandourh Masahel Almutairi, ‎‏Maryam Farhan Al-Anazi, Reem Abdulmoeen Alotaibi; Nawal Ibrahim Fallatah, Shoaa Abdullah Shaaf Alenazi, Fahad Abdulla Mohammed Alshahrani, Nada Yahya Hassen Motashesh (Journal of International Crisis and Risk Communication Research, 2024)
Dental assistants play a pivotal role in modern dentistry, bridging the gap between dental teams and patients. Dental assistants are multi-tasking and multi-tasking professionals, assisting dentists with therapeutic interventions, infection control, managing administrative workflows, and leveraging digital tools. In modern dentistry, dental assistants face challenges such as workplace stress, role overlapping, and rapid adaptation to emerging technologies. Addressing these challenges through structured career paths, enhanced training, and integration of advanced tools is vital to improving their efficiency and job satisfaction. This review explores the competencies, challenges, and prospects of dental assistants, emphasizing the need for continuing education and technological proficiency to meet modern demands.